2013
DOI: 10.3141/2350-13
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Evaluation of Rail Systems in Mass Events

Abstract: Each year during the ninth month of the Muslim lunar calendar, more than 2 million Muslim pilgrims from around the world travel to the Holy City of Mecca in Saudi Arabia for Hajj, an annual religious pilgrimage. A significant milestone in the effort to improve the existing transport system in the Holy City was the introduction of the Southern Masha'er Rail Line during the 2010 pilgrimage season. In the first year of operation, the line operated at only 30% of its full capacity before full implementation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…All the rituals of hajj are carried out by more than three million pilgrims and all the rituals are bound to time and place. 31,32 Crowd Management is one of the main issues since millions of pilgrims have to perform all the rituals within 5 to 6 days in destined places. Many tragedies happened in the history of Hajj Pilgrimage due to stampede and other accidents.…”
Section: About Hajjmentioning
confidence: 99%
“…All the rituals of hajj are carried out by more than three million pilgrims and all the rituals are bound to time and place. 31,32 Crowd Management is one of the main issues since millions of pilgrims have to perform all the rituals within 5 to 6 days in destined places. Many tragedies happened in the history of Hajj Pilgrimage due to stampede and other accidents.…”
Section: About Hajjmentioning
confidence: 99%
“…An optimization method was suggested by Felemban et al [ 107 ] to schedule the movement of pilgrims using the train during the Hajj days, as previously tested in research [ 25 , 31 ]. The authors of [ 107 ] identified three factors that affect the scheduling process, which are the type of train movement, the location of the pilgrim camp, and the camps to the permitted stations and vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IoT Technologies and their applications have also gained tangible attention in the Hajj and Umrah crowd systems [ 23 , 24 ], which their impact evident in many places in the two holy cities, Makkah and Madinah, including the two holy mosques, the holy sites, galleries, libraries, and museums [ 25 ]. As considered, Hajj is one of the Five Pillars of Islam, the basic acts that all Muslims are supposed to perform at least once in life.…”
Section: Introductionmentioning
confidence: 99%
“…These religious visitors are known as Al-Rahman guests pretending their main purpose of visiting is the holy lands and holy house of Allah. Many government and private sectors provide various services to Al-Rahman guests to facilitate their worships performance (Kaysi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%